Left Vocal Cord Paralysis Detected by PET/CT in a Case of Lung Cancer - Ali Ozan Oner; Adil Boz; Evrim Surer Budak; Gulnihal Hale Kaplan Kurt (Case Reports in Oncological Medicine)
We report a patient with lung cancer. The first PET/CT imaging revealed hypermetabolic mass in the left aortopulmonary region and hypermetabolic nodule in the anterior segment of the upper lobe of the left lung. After completing chemotherapy and radiotherapy against the primary mass in the left lung, the patient underwent a second PET/CT examination for evaluation of treatment response. This test demonstrated, compared with the first PET/CT, an increase in the size and metabolic activity of the primary mass in the left lung in addition to multiple, pathologic-sized, hypermetabolic metastatic lymph nodes as well as multiple metastatic sclerotic areas in bones. These findings were interpreted as progressive disease. In addition, an asymmetrical FDG uptake was noticed at the level of right vocal cord. During follow-up, a laryngoscopy was performed, which demonstrated left vocal cord paralysis with no apparent mass. Thus, we attributed the paralytic appearance of the left vocal cord to infiltration of the left recurrent laryngeal nerve by the primary mass located in the apical region of the left lung. In conclusion, the knowledge of this pitfall is important to avoid false-positive PET results.